Fort Scott, Bourbon County - Blake, Daron (Kansas State University, The Chapman Center for Rural Studies, 2011)
This paper examines the development of Fort Scott, Kansas from 1890 to 1920 and compares this small city with other towns in southeastern Kansas at the time. The diversification of industry brought by the railroad, combined with a stabilized population level, transformed Fort Scott into a small industrial city unique in southeastern Kansas for its strong sense of community of a smaller town and the industrial diversity of a larger city.
Daron Blake, “Fort Scott, Bourbon County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/14.
Keywords: Bourbon County; William Cutler; Cherokee-Crawford Coal deposits; Fort Scott; Parkinson Sugar Works; Gulf railroad